Exploring Students' Potential: Constructivism Approach in Arabic Language Learning - Setiadi, Fadlan Masykura; Zulpina; Kamaluddin Nurdin Marjuni (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
This study aimed to explore students' potential through a constructivism approach to Arabic language learning. This study employed a descriptive qualitative, this research analyzes the impact of the constructivism approach on students' engagement, understanding, and critical thinking in the context of Arabic language learning. Data were collected through observations, interviews, and document studies in two Arabic language classes at SD-IT Al-Furqan and SD-IT Adnani. The results indicated that the constructivism approach can enhance students' engagement, communication skills, and critical thinking abilities. Students involved in constructivism-based activities show significant improvements in language understanding, the application of language concepts in real-world contexts, as well as reflective and collaborative skills. These findings showed that constructivist learning can play a crucial role in optimizing students' potential in Arabic language learning. The study recommends greater support for teachers in implementing this approach and further exploring its long-term impact on Arabic language learning.